Strand 1: Pedagogy and Design: The Relationship Between Educational Theory & Research and Networked Learning Practice - Banks, Sheena; McConnell, David; Graebner, Celia (Proceedings of the International Conference on Networked Learning, 2025)
With the recent national initiatives around lifelong learning, particularly the National Grid for Learning, we are seeing in the United Kingdom the opening up of a broad consultation around educational change in which we can begin to draw on the experiences of the many networked learning pilot programmes scattered across various sectors of education and training.